Managerial Based on TQM in Delivering Quality Service Padang State University Library - Rahmah, Elva; Marlini, Marlini (Record and Library Journal, 2018)
Background of the study: TQM or commonly referred to as Total Quality Management organizational culture is focused on the achievement of quality and enhance sustainable manner through every activity of the organization.Purpose: This study specifically aims to: (1) determine the understanding of leadership and staff to the concepts of TQM in the Library of Padang State University (UNP); (2) obtain a picture of how the managerial based TQM activities undertaken to realize the quality of library services in the UNP.Method: This study used descriptive qualitative method. The data collection was done by interview, observation, and analyzing data.Findings: The subjects were leaders, heads of sub-section, the library staff, user, events, facts, documents and other forms of efforts, programs or activities of the library.Conclusion: The object of this research is carried out TQM system in the library of the UNP.